Voices of discomfort: metaphorical conceptualisations of physical pain in Algerian Arabic - Rababah, Ghaleb; Nesba, Kaouther; Alghazo, Sharif; Abusalim, Nimer; Rayyan, Mohammad (Frontiers in Communication, 2024)
This study investigates the metaphorical representations of physical pain amongst Algerian Arabic speakers. To uncover these conceptualisations, an oral Discourse Completion Test (DCT) was administered to 30 Algerian university students. A qualitative approach was used to analyse the data and generate the conceptual metaphors used. Grounded in Kövecses model of metaphorical conceptualisations, this research unveils that Algerian Arabic speakers utilise nine distinct metaphorical conceptualisations when portraying physical pain/discomfort: evaluative metaphors, fire metaphors, sharp object metaphors, container metaphors, animal metaphors, creeping insect metaphors, burden metaphors, swing metaphors, and physical force metaphors. These metaphors are further explicated in light of linguistic and cultural backgrounds to shed light on the intricate weave of metaphors in Algerian Arabic, underscoring their pivotal role in encapsulating physical and emotional experiences. The study recommends further scholarly research into the manifold metaphorical renderings of diverse emotional states across Arab communities.